2019
DOI: 10.1051/0004-6361/201936275
|View full text |Cite
|
Sign up to set email alerts
|

Shock-accelerated cosmic rays and streaming instability in the adaptive mesh refinement code Ramses

Abstract: Cosmic rays (CRs) are supposed to play a dynamical important role on several key aspects of galaxy evolution, including the structure of the interstellar medium, the formation of galactic winds, and the non-thermal pressure support of halos. We introduce a numerical model solving for the CR streaming instability and acceleration of CRs at shocks with a fluid approach in the adaptive mesh refinement code ramses. CR streaming is solved with a diffusion-like approach and its anisotropic nature is naturally captur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 102 publications
(146 reference statements)
1
35
0
Order By: Relevance
“…With a proper refinement criteria, the AMR grid is a powerful tool to study multi-scale problems such as the protostellar collapse of a dense core. The RAMSES code is very proficient for problems that require a treatment of magnetohydrodynamics (Teyssier et al 2006;Masson et al 2012;Marchand et al 2018;Marchand et al 2019), radiation hydrodynamics Rosdahl et al 2013;Commerçon et al 2014;Rosdahl & Teyssier 2015;González et al 2015;Mignon-Risse et al 2020) or cosmic rays (Dubois & Commerçon 2016;Dubois et al 2019). We extended the code to the treatment of dust dynamics with multiple species in the diffusion approximation and terminal velocity regime (Lebreuilly et al 2019).…”
Section: Ramsesmentioning
confidence: 99%
“…With a proper refinement criteria, the AMR grid is a powerful tool to study multi-scale problems such as the protostellar collapse of a dense core. The RAMSES code is very proficient for problems that require a treatment of magnetohydrodynamics (Teyssier et al 2006;Masson et al 2012;Marchand et al 2018;Marchand et al 2019), radiation hydrodynamics Rosdahl et al 2013;Commerçon et al 2014;Rosdahl & Teyssier 2015;González et al 2015;Mignon-Risse et al 2020) or cosmic rays (Dubois & Commerçon 2016;Dubois et al 2019). We extended the code to the treatment of dust dynamics with multiple species in the diffusion approximation and terminal velocity regime (Lebreuilly et al 2019).…”
Section: Ramsesmentioning
confidence: 99%
“…It has been demonstrated that stable numerical solutions are achievable due to the regularization. Uhlig et al (2012) and later on Dubois et al (2019) showed that streaming can be recasted into a diffusion term and be solved with an implicit solver for diffusion. The streaming transport term in the CR energy equation $…”
Section: Unified Alfvén Wave Regulated Cr Transportmentioning
confidence: 99%
“…This result is independent of the assumed magnetic coherence length. Dubois et al (2019) use a similar approach to inject CRs at the loci of the MHD shocks with an on-the-fly shock finder in the larger boxes of the interstellar medium using RAMSES. The efficiency is also coupled to the upstream magnetic obliquity.…”
Section: Crs In the Interstellar Mediummentioning
confidence: 99%
“…turbulence damping). Of course, there exist a variety of complexities in the above argument that make it highly uncertain; however, it seems likely that such questions may only be answered definitively with detailed simulations of the streaming instability, which are only recently becoming possible (Bai et al 2019;Dubois et al 2019;Haggerty & Caprioli 2019;Holcomb & Spitkovsky 2019;Weidl, Winske & Niemann 2019).…”
Section: Polarizationmentioning
confidence: 99%